2023
DOI: 10.1101/2023.01.17.23284675
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trans-ethnic Polygenic Risk Scores for Body Mass Index: An International Hundred K+ Cohorts Consortium Study

Abstract: Background While polygenic risk scores hold significant promise in estimating an individual's risk of developing a complex trait such as obesity, their application in the clinic has, to date, been limited by a lack of data from non-European populations. As a collaboration model of the International Hundred K+ Cohorts Consortium (IHCC), we endeavored to develop a globally applicable trans-ethnic PRS for body mass index (BMI) through this relatively new international effort. Methods The PRS model was developed t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our data showed that the TE PRS outperformed the ancestry‐specific models in the Chinese and Brazilian populations, whereas there is no appreciable loss in predictive power in European ancestry individuals when using a TE score. However, as shown in our study, the TE PRS for BMI has a poor performance in the admixed Brazilian population, although it outperforms the European PRS 42 . Increased genetic diversity and unique genetic drift and selection pressures contribute different LD patterns.…”
Section: Te Prs For Bmisupporting
confidence: 48%
See 2 more Smart Citations
“…Our data showed that the TE PRS outperformed the ancestry‐specific models in the Chinese and Brazilian populations, whereas there is no appreciable loss in predictive power in European ancestry individuals when using a TE score. However, as shown in our study, the TE PRS for BMI has a poor performance in the admixed Brazilian population, although it outperforms the European PRS 42 . Increased genetic diversity and unique genetic drift and selection pressures contribute different LD patterns.…”
Section: Te Prs For Bmisupporting
confidence: 48%
“…Currently, the performance of PRS for BMI prediction is relatively modest. Our recent PRS model for extreme BMI, that is, the top 1% and 5% has a moderate AUC of 0.703–0.736 with an acceptable predictive power in two large European populations, the Nurses’ Health Study (NHS) and Nurses’ Health Study II (NHSII) 42 . As further research and advancements continue, the BMI‐PRS model is expected to evolve and enhance its predictive power, ultimately contributing to more effective obesity prevention and treatment strategies.…”
Section: Polygenic Risk Score (Prs) For Bmimentioning
confidence: 97%
See 1 more Smart Citation
“…Most recently, Qu et al 5 . addressed this limitation in the application of PRS for body mass index (BMI) in non‐European populations.…”
mentioning
confidence: 99%